And the dragons arrived: dregdes and drugs on the caquetá river (police inspection of metá, finca “el refugio”) (2014)
This text relates the history of the arrival of alluvial mining to the Middle Caquetá region (Colombian Amazon). It is narrated from the experience of one of the leaders of the Multiethnic Community of Quinché-Metá, formed by indigenous peoples from several ethnic groups and homesteaders, which aimed to organize as a multiethnic Resguardo (legally constituted indigenous territory) at the beginning of the 21st Century. The text begins with the narration of this organizing process and what had been achieved. Then it tells about the arrival of the mining rafts, together with the guerilla and drug dealers, and how it quickly eroded the process and the abuses and killings escalated. The text also tells about other experiences with gold extraction in the Taraira River. It concludes with the “reconquest” of the region by the Colombian army and how ten years after, in 2012, once again the miners are returning to the Caquetá River.